Real-life experience after 3 months with tezepelumab before marketing approval - Villalobos Violán, Victoria; González Cano, Beatriz; Ángel Racionero Casero, Miguel; González-Mancebo, Eloína; Mohedano Vicente, Esther; Trujillo Trujillo, María Jesús; Gandolfo-Cano, Mar (Allergologia et Immunopathologia, 2023)
Background: Tezepelumab is a monoclonal antibody targeting thymic stromal lymphopoietin (TSLP), implicated in asthma pathogenesis, and that has been approved for patients with severe uncontrolled asthma in Spain in October 2023. This study evaluates our experience with Tezepelumab for those patients who received the indicated drug off-label prior to its commercialization. Methods: We conducted a real-life observational study on three patients from the Severe Asthma Unit of the Hospital Universitario de Fuenlabrada, Spain, who received Tezepelumab off-label before its official approval. We analyzed symptoms control based on ACT, exacerbations, reductions in the doses of oral corticosteroid, lung function, blood changes and safety at 3 months of treatment. Results: Tezepelumab demonstrated efficacy in improving asthma control and a notable reduction in emergency department visits. OCS use decreased, with one patient halving their prednisone dose. Lung function, particularly FEV1 and FEV1/FVC parameters, improved, but no significant changes were observed in FeNO levels, blood eosinophil counts and total IgE. The treatment exhibited a favorable safety profile with no reported adverse effects during the study period. Conclusions: In this preliminary real-world experience prior to the official approval of tezepelumab in Spain, this monoclonal antibody showed promising results and suggests its potential as a valuable alternative for the treatment of severe asthma.